2021
DOI: 10.7861/fhj.2020-0112
|View full text |Cite
|
Sign up to set email alerts
|

The role of extended reality technology in healthcare education: Towards a learner-centred approach

Abstract: The use of extended reality (XR) technologies is growing rapidly in a range of industries from gaming to aviation. However, how this technology should be implemented in healthcare education is not well-documented in the literature. Learner-driven implementation of educational technology has previously been shown to be more effective than a technology-driven approach. In this paper we conduct a narrative literature review of relevant papers to explore the role of XR technologies in learner-driven approaches to … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
23
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 78 publications
(38 citation statements)
references
References 42 publications
(63 reference statements)
0
23
0
Order By: Relevance
“…In this context, digital anatomy resources provide sophisticated tools for preoperative study, particularly complex surgical planning [ 45 - 47 , 49 ] ( Table 1 ). Although digital anatomy has unique attributes that can improve learning outcomes when compared with traditional learning methods [ 32 ], there is currently a shortfall in learner-centered implementation of digital technologies in health care education, where these technologies have the capacity to cause a paradigm shift ( Table 1 ).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…In this context, digital anatomy resources provide sophisticated tools for preoperative study, particularly complex surgical planning [ 45 - 47 , 49 ] ( Table 1 ). Although digital anatomy has unique attributes that can improve learning outcomes when compared with traditional learning methods [ 32 ], there is currently a shortfall in learner-centered implementation of digital technologies in health care education, where these technologies have the capacity to cause a paradigm shift ( Table 1 ).…”
Section: Resultsmentioning
confidence: 99%
“…Junior medical students perceive the use of virtual dissection as a valuable tool for learning anatomy and radiology [ 27 ]. Evaluation of the effectiveness of anatomical education using digital technologies, including AR, VR, and MR, supports several pedagogy measurements, including student experience and satisfaction [ 23 , 24 , 28 , 30 , 31 ], learning performance and outcome [ 25 - 27 , 29 , 31 , 32 ], problem-solving skills and clinical reasoning [ 32 , 33 ], and postintervention knowledge and skills outcomes [ 34 - 36 ], with or without comparison with traditional teaching. Overall, these studies support the premise of applying digital anatomy as a means of curriculum development for more surgical-oriented training.…”
Section: Introductionmentioning
confidence: 93%
“…The technology stimulates a user’s multiple senses, enabling the user to interact with realistic 3D virtual environments [ 5 , 8 ]. VR is different from augmented reality, which is another type of extended reality technology; while augmented reality superimposes digital data onto the real world, VR shuts out the real world and provides interaction with the simulated virtual world [ 9 ]. Simulated virtual worlds can be delivered in a nonimmersive or immersive manner.…”
Section: A Brief Look At Virtual Realitymentioning
confidence: 99%
“…Ong et al [59] Ophthalmology Ophthalmoscopy simulators Improves procedural success and reduces complication rates in ophthalmic surgery. Logeswaran et al [60] Healthcare education Pedagogical models Improved learning outcomes were identified through learnercentred models. Kosko et al [61] Teacher education Representations of practice Perceptual capacity assessment for theory and practice was performed.…”
Section: Xr Technologies For Metaversementioning
confidence: 99%